2019
DOI: 10.21203/rs.2.13455/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Management and leadership competence for hospital managers: a systematic review and best fit framework synthesis

Abstract: Background Competent managers are vital to the productivity and service quality of healthcare organizations and the sustainability of the healthcare system including hospitals. The purpose of this study is to synthesize the evidence related competency to management and leadership in healthcare organizations including hospitals through the Best Fit Method. Methods A systematic literature review was performed to identify studies focusing on confirming and/or assessing the competency requirements of health servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(56 reference statements)
1
8
0
2
Order By: Relevance
“…According to our results, managers need to be able to justify their decisions based on knowledge. Thus, our results emphasize knowledge management, which is congruent with a previous study (Kakemam et al, 2020). In accordance to our study, previous research has found that managers need to have adequate IT skills (Collins et al, 2017;Ingebrigtsen et al, 2014;Strudwick et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to our results, managers need to be able to justify their decisions based on knowledge. Thus, our results emphasize knowledge management, which is congruent with a previous study (Kakemam et al, 2020). In accordance to our study, previous research has found that managers need to have adequate IT skills (Collins et al, 2017;Ingebrigtsen et al, 2014;Strudwick et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…One of the aims of this study was to examine differences in management competencies between different levels of management. Previous studies have identified the need for a review between management levels in management competencies (Kakemam et al, 2020;. This study brings novelty value to this topic.…”
Section: Discussionmentioning
confidence: 88%
“…While management is described as the process of organising, leading, and controlling human, material, financial and informational resources in an organisational context in order to achieve predetermined goals (Swansburg & Swansburg, 2002). The competencies encompassed by these two concepts were overlapped and comprise components of the core competencies of nursing managers jointly (Kakemam et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Kanerva et al (2017) suggest that leadership development is a crucial element in advancing patient safety in hospitals. Reviews by Kakemam et al (2020) and Lunden et al (2017) emphasized that nurse leaders need evidence‐based interventions to support shared learning and create infrastructure that facilitates competence development.…”
Section: Introductionmentioning
confidence: 99%